PENGARUH MODAL SENDIRI DAN MODAL PINJAMAN TERHADAP SISA HASIL USAHA PADA KOPERASI DOSEN DAN KARYAWAN UNIVERSITAS SLAMET RIYADI SURAKARTA - Santosa, Ridho Nugroho Putra; Rispantyo, Rispantyo (Universitas Slamet Riyadi, 2019)
The purpose of this research is to analyze the significance of the influence of private equity and loan capital simultaneously significant effect against the rest of the results of efforts at Cooperative University Faculty and employees of the Slamet Riyadi. Research methods method using case studies, the data type of the data being used is qualitative and quantitative data, the source data used the data of secondary. Method of data collection used documentation. Technique of data analysis used a classic assumption test, multiple linear regression analysis, t-test, F-test and coefficient of determination. The research results obtained the conclusion that there is a significant and positive influence on the capital of its own against the rest of the business results. Capital lending significant negative effect against the rest of the business results. Private equity and loan capital in the influential simultan significantly to the rest of the business results.